A Semantic-Pragmatic Investigation of Meaning Construction Among Indonesian EFL Learners - Susi Fatresia; Maharani, Maharani; Parera, Rosariani; Syam, Ulfa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Meaning construction in English as a Foreign Language (EFL) classrooms extends beyond understanding the literal meanings of words. It involves secondary school learners' ability to integrate semantic knowledge with pragmatic interpretation while responding appropriately to contextual, interpersonal, and sociocultural cues. This study investigates how Indonesian secondary school EFL learners construct meaning during classroom interaction by examining the interplay among teacher talk, semantic competence, pragmatic competence, Self-Perceived Communication Competence (SPCC), and Willingness to Communicate (WTC). Employing a qualitative case study design at a secondary school in Makassar, data were collected from English teachers and secondary school students through classroom observations, audio-video recordings, semi-structured interviews, and field notes. Classroom discourse was analyzed using Martin and White's Appraisal Theory, while interview data were analyzed thematically following Miles, Huberman, and Saldaña's interactive model. Findings indicate that positive teacher talk contributes to a psychologically supportive classroom environment that enhances learners' communication confidence and encourages active participation in meaning negotiation. Semantic competence alone is insufficient; learners' pragmatic competence and contextual awareness play essential roles in interpreting implied meanings and indirect speech acts. Secondary school learners with stronger SPCC demonstrate higher WTC and more effective meaning negotiation. Meaning construction is thus a multidimensional process emerging from the interaction among linguistic competence, classroom discourse, and learners' psychological readiness.